SMART CONTRACTS - RETROSPECTIVE ANALYSIS (European Journal of Interdisciplinary Research and Development, 2024)
In this article, the civil-legal nature of smart contracts is researched and relevant conclusions are drawn. In this scientific work, the relevance, purpose and tasks of the research, the level of research of the problem, the object and the subject are given, and the conclusions and proposals reached based on the results of the research are reflected.